2008
DOI: 10.1016/j.yexcr.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated telomere shortening and replicative senescence in human fibroblasts overexpressing mutant and wild-type lamin A

Abstract: LMNA mutations are responsible for a variety of genetic disorders, including muscular dystrophy, lipodystrophy, and certain progeroid syndromes, notably Hutchinson-Gilford Progeria. Although a number of clinical features of these disorders are suggestive of accelerated aging, it is not known whether cells derived from these patients exhibit cellular phenotypes associated with accelerated aging. We examined a series of isogenic skin fibroblast lines transfected with LMNA constructs bearing known pathogenic poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 61 publications
6
95
1
1
Order By: Relevance
“…Some reports indicate that hTERT-mediated cellular immortalization is possible in certain HGPS strains (34,44,45), while others have found that HGPS fibroblasts are resistant to hTERT immortalization (46,47). Moreover, hTERT does not protect against progerin-induced aberrant nuclear shape and DNA damage (48).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicate that hTERT-mediated cellular immortalization is possible in certain HGPS strains (34,44,45), while others have found that HGPS fibroblasts are resistant to hTERT immortalization (46,47). Moreover, hTERT does not protect against progerin-induced aberrant nuclear shape and DNA damage (48).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that the expression of lamin A (E145K progeria mutation) induced the formation of blebs in the nuclear membrane in which lamin B1 was excluded. 30 Another studies show that deletion of lamin B1 increases the size of the Lamin A/C meshwork and induces the formation of lamin A/C-rich and lamin B2-deficient NE blebs 32 23,[33][34][35][36] In contrast with HGP fibroblasts, the telomere length in hematopoietic cells, which typically do not express lamin A, was within the normal range in different HGPS patients' samples. These results suggest that expression of mutant lamin A is necessary for telomere loss in HGPS.…”
Section: Lamin Levels Must Be Tightly Controlled For the Maintenance mentioning
confidence: 99%
“…The silencing of lamin A results in NSA and senescence. On the other hand, the overexpression of the full length wild-type cDNA results also in growth defects, dysmorphic nuclei and senescence, [21][22][23] however the picture is more complex due to maturation of the lamin A protein.…”
Section: Lamin Levels Must Be Tightly Controlled For the Maintenance mentioning
confidence: 99%
“…Cells derived from HGPS patients, like cells derived from patients with other progeroid syndromes, have been reported to undergo premature senescence (Huang et al, 2005(Huang et al, , 2008. However, in the case of HGPS patient-derived cells, no isogenic and simultaneously derived control fibroblasts have been available for direct comparison.…”
Section: Long-term Culturing Of Mutant Lamin A-expressing Cellsmentioning
confidence: 99%